1992
DOI: 10.1159/000126146
|View full text |Cite
|
Sign up to set email alerts
|

Physical Stress in the Middle of the Dark Phase Does Not Affect Light-Depressed Plasma Melatonin Levels in Humans

Abstract: The human pineal gland has been shown to be unresponsive to stress-induced sympathetic activation during the day. However, the effects of stress on human melatonin production have received little investigation at night, when the pinealocytes should be physiologically responsive to noradrenergic stimulation. For this purpose, plasma melatonin and cortisol levels were measured in 7 healthy men (aged 25–34 years), both in resting condition and before and after a physical exercise performed between 23.40 and 24.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…A standardized light meal was given to each participant at 3 h before starting the tests. Subjects were also maintained in standard conditions throughout the tests: light intensity in the laboratory was about 30 lux, to exclude effects of light exposure on endogenous melatonin secretion (Monteleone et al 1992); ambient temperature was 23 ± 0.6°C and relative humidity was 48 ± 7%. For 24 h prior to each trial, participants were required to abstain from intakes of alcohol and non-steroidal anti-inflammatory drugs; they were also asked not to participate in any strenuous exercise for at least two days prior to each trial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A standardized light meal was given to each participant at 3 h before starting the tests. Subjects were also maintained in standard conditions throughout the tests: light intensity in the laboratory was about 30 lux, to exclude effects of light exposure on endogenous melatonin secretion (Monteleone et al 1992); ambient temperature was 23 ± 0.6°C and relative humidity was 48 ± 7%. For 24 h prior to each trial, participants were required to abstain from intakes of alcohol and non-steroidal anti-inflammatory drugs; they were also asked not to participate in any strenuous exercise for at least two days prior to each trial.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Reilly et al (2007) showed that mental performance tended to peak around noon, and various studies have investigated the effects of nocturnal exercise on the different components of sleep. For example, Monteleone et al (1992) showed that physical exercise at night blocks the nocturnal increase of melatonin and increases plasma cortisol levels in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MLT consumption increased average speed, ambulatory time, and distance traveled in retrovirally infected, young mice in comparison to uninfected controls. Exercise can elevate (26) or decrease MLT levels (27)(28). MLT supplementation enhances immunity in AIDS and retroviral infection (29,25) although exercise can elevate (26) or decrease MLT levels (27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies report that melatonin levels decrease, increase or remain unaffected by physical activity [44][45][46][47][48][49][50]. This variability in melatonin response to exercise can be explained by time of day, light conditions, type, duration or intensity of exercise, and by melatonin sampling scheme.…”
Section: Melatoninmentioning
confidence: 99%